Modification Research of the Internal Substructure Method for Seismic Wave Input in Deep Underground Structure-Soil Systems - Xin Bao; Jingbo Liu; Dongyang Wang; Shutao Li; Fei Wang; Xiaofeng Wang (Shock and Vibration)
A new internal substructure method for seismic wave input in soil-structure systems was recently proposed. This method simplifies the calculation of equivalent input seismic loads and avoids the participation of artificial boundaries in the process of seismic wave input. However, in previous research and applications, the internal substructures are usually intercepted down from the free surface, which forms large substructures and increases the computational effort for data management on the substructure nodes, especially for deep underground structures. In this study, the internal substructure method is modified by intercepting the internal substructures entirely beneath the free surface and adjacently around the underground structures. Then, the equivalent input seismic loads are obtained through the dynamic analysis of the internal substructures and applied to the corresponding positions of the total soil-structure models. Thus, the earthquake energy can be more efficiently input into the region near the underground structures without losing computational accuracy. We provide the detailed implementation procedures of this modified method and validate its applicability and accuracy through the scattered problems of underground cavities in homogeneous and layered half-space sites.